DIRAE 15: AN EMENDATION. (8th November 2018) - Kayachev, Boris
Abstract : Here, too, it may initially appear reasonable to see in uobis the same group of people, but there is little doubt that it must refer to senis nostri felicia rura, which can hardly be anything but a vocative (cf. 33 ueteris domini felicia ligna, likewise a vocative). If condatis does not refer to people, one may be tempted to accept the humanist conjecture sulci and construe the verb as addressed to the furrows. Yet I rather doubt that an address to the farm (or to the grove, as at line 33, or to the springs and the fields, as at line 90) can justify apostrophizing something as technical and down-to-earth as furrows. I think Fraenkel is right to insist on relating condatis to the same vocative as uobis, that is, rura . This interpretation is supported by the fact that the two stanzas are closely analogous (as we soon shall see in greater detail).